Examining Supervisor and Supervisee Agreement on Alliance: Is Shame a Factor? - Bilodeau, Cynthia; Savard, Réginald; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2010)
This study examined the agreement of 31 supervisee-supervisor pairs on perceived strength of working alliance throughout 5 supervision sessions and on whether the alliance differed significantly in relation to supervisee shame-proneness. The Supervisory Working Alliance Inventory (Trainee and Supervisor versions) was used to measure the working alliance, and the Internalized Shame Scale was used to measure supervisee shame-proneness. Repeated measures analysis of variance revealed a lack of concordance between perceived alliance strength of supervisors and supervisees (F(1,29) = 12.70, p = 0.0013). No differences in alliance ratings were found in relation to shame-proneness. Implications for supervision are discussed.